2017
DOI: 10.1371/journal.pone.0181960
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with depression in people living with HIV in sub-Saharan Africa: A systematic review and meta-analysis

Abstract: Depression, one of the most common psychiatric disorders, is two- to three-times more prevalent in people living with HIV (PLHIV) than in the general population in many settings as shown in western countries but remains neglected in sub-Saharan Africa (SSA). We aimed to summarize the available evidence on the prevalence of depression and associated factors according to the scales used and the treatment status in PLHIV in SSA. The pooled prevalence estimates of depression ranged between 9% and 32% in PLHIV on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
187
7
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(219 citation statements)
references
References 79 publications
19
187
7
6
Order By: Relevance
“…Even though highly active antiretroviral therapy (HAAR T) helped patients to live longer and healthier lives, it is accompanied with numerous challenges in terms of associated symptoms and treatment side effects [5][6][7]. Fatigue is one of the most frequently reported symptoms by HIV/ Acquired Immune Deficiency Syndrome (HIV/AIDS) patients [8,9], which is defined as a 'subjective sensation of weariness, increasing sense of effort, mismatch between effort expended and actual performance, or exhaustion which is not relived by additional sleep or rest' [10].…”
Section: Introductionmentioning
confidence: 99%
“…Even though highly active antiretroviral therapy (HAAR T) helped patients to live longer and healthier lives, it is accompanied with numerous challenges in terms of associated symptoms and treatment side effects [5][6][7]. Fatigue is one of the most frequently reported symptoms by HIV/ Acquired Immune Deficiency Syndrome (HIV/AIDS) patients [8,9], which is defined as a 'subjective sensation of weariness, increasing sense of effort, mismatch between effort expended and actual performance, or exhaustion which is not relived by additional sleep or rest' [10].…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety change over time and studies examining such conditions at a single time point will not represent their course and progression [11]. Although an overwhelming majority of cross-sectional studies have demonstrated the prevalence and related factors of depression and anxiety among people living with HIV, the results have been fragmentary and inconsistent [12][13][14][15]. Findings of the few existing longitudinal studies have also been mixed [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Even though highly active antiretroviral therapy (HAART) helped patients to live longer and healthier lives, it is accompanied with numerous challenges in terms of associated symptoms and treatment side effects [5][6][7]. Fatigue is one of the most frequently reported symptoms by HIV/AIDS patients [8,9], which is defined as a 'subjective sensation of weariness, increasing sense of effort, mismatch between effort expended and actual performance, or exhaustion which is not relived by additional sleep or rest' [10].…”
Section: Introductionmentioning
confidence: 99%